2017
DOI: 10.1002/anie.201710053
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Suzuki Biaryl Coupling of Aryl Halides

Abstract: Readily accessed cobalt pre‐catalysts with N‐heterocyclic carbene ligands catalyze the Suzuki cross‐coupling of aryl chlorides and bromides with alkyllithium‐activated arylboronic pinacolate esters. Preliminary mechanistic studies indicate that the cobalt species is reduced to Co0 during the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 28 publications
0
35
2
Order By: Relevance
“…T he molecular structure of 13 was clarified by single-crystal X-ray diffraction analysis and shows adistorted tetrahedral geometry,inwhich both C=Cd ouble bonds of dvtms coordinate to the cobalt center in a h 2 -fashion. Thebond lengths of C=C ave (1.32 )on the dvtms moiety are significantly shorter than those of previously reported for phosphine-and carbene-coordinated cobalt analogues,Co(dvtms)(PMe 3 ) 2 (C = C ave = 1.41 ) [11] and Co(dvtms)(IPr) (C = C ave = 1.42 ), [12] probably owing to the weak s-bonding and strong p-back bonding nature of the phenanthroline ligand compared with PMe 3 and IPr. The bulkier aryl substituents at the 2,9-positions of 1,10-phenanthroline surrounds the cobalt(0) center, suppressing the decomposition as well as formation of ab is(phenanthroline)cobalt(0) species.T he spin-density plots of 13 obtained by density-functional theory (DFT) calculations clarified that the unpaired electron is primarily localized on the cobalt center, which is consistent with the electron configuration of Co 0 .T he complex 13 catalyzed the cross-dimerization of 2a and 3 without any reductant to give Table 2: Substrate scope of alkynyl acceptors for the cross-dimerization of terminal alkynes.…”
mentioning
confidence: 55%
“…T he molecular structure of 13 was clarified by single-crystal X-ray diffraction analysis and shows adistorted tetrahedral geometry,inwhich both C=Cd ouble bonds of dvtms coordinate to the cobalt center in a h 2 -fashion. Thebond lengths of C=C ave (1.32 )on the dvtms moiety are significantly shorter than those of previously reported for phosphine-and carbene-coordinated cobalt analogues,Co(dvtms)(PMe 3 ) 2 (C = C ave = 1.41 ) [11] and Co(dvtms)(IPr) (C = C ave = 1.42 ), [12] probably owing to the weak s-bonding and strong p-back bonding nature of the phenanthroline ligand compared with PMe 3 and IPr. The bulkier aryl substituents at the 2,9-positions of 1,10-phenanthroline surrounds the cobalt(0) center, suppressing the decomposition as well as formation of ab is(phenanthroline)cobalt(0) species.T he spin-density plots of 13 obtained by density-functional theory (DFT) calculations clarified that the unpaired electron is primarily localized on the cobalt center, which is consistent with the electron configuration of Co 0 .T he complex 13 catalyzed the cross-dimerization of 2a and 3 without any reductant to give Table 2: Substrate scope of alkynyl acceptors for the cross-dimerization of terminal alkynes.…”
mentioning
confidence: 55%
“…Organosodium chemistry has long been overshadowed by the well-established organolithium chemistry. While there has been some recent renewed interest in the use of organosodium compounds for organic synthesis, 26,27,28,29,30,31,32 the alkylsodium reagent can be conveniently and freshly prepared in situ using an inexpensive alkyl chloride and an easy-to-handle sodium dispersion, circumventing the need for hazardous storage; 2) the sodium dispersion in paraffin at 26 wt% concentration is easy to handle and less hazardous; 18 this is a practical advantage, considering that organolithiums are highly pyrophoric and hazardous to use and store, and are the cause of many accidents in organic laboratories; 3) the reactions proceed typically at 0 °C using an ice bath; 4) sodium is ubiquitous, abundant, inexpensive, and therefore less vulnerable to supply risks. Thus, we believe that the reaction described here has the potential to replace the textbook halogen-lithium exchange, and open new frontiers for establishing organosodium-based sustainable organic chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…We have been exploring the potential of organosodium for organic synthesis for a while, 16,17 and have recently reported that arylsodiums can be conveniently prepared by two-electron reduction of aryl chlorides with an easy-to-handle and highly reactive fine dispersion (particle size smaller than 10 mm) of sodium in paraffin oil (sodium dispersion; SD), 18 and subsequently participate in Negishi, Suzuki-Miyaura, and direct cross-coupling reactions (Figure 1c). 16,19 However, this method could only be applied for the preparation of a narrow range of organosodium compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…61 The deactivation mechanisms of catalysts based on 4d and 5d metals can thus provide useful insight for the development of new systems based on the cheaper and less toxic 3d metals. 62,63,64,65,66,67 Despite the biased attention of mechanistic studies towards on-cycle steps, a fair amount of data is already available for off-cycle deactivation reactions. The topic was recently reviewed by Crabtree, who classified these reactions on the basis of their cause, including ligand-centered reactions and inhibition by different agents, and discussed how they can be excluded or mitigated.…”
Section: Sophisticated Models Based On Quantum Mechanics Calculationsmentioning
confidence: 99%